Field-Free Magnetization Switching in a Ferromagnetic Single Layer through Multiple Inversion Asymmetry Engineering - Huang, Qikun; Guan, Chaoshuai; Fan, Yibo; Zhao, Xiaonan; Han, Xiang; Dong, Yanan; Xie, Xuejie; Zhou, Tie; Bai, Lihui; Peng, Yong; Tian, Yufeng; Yan, Shishen (ACS nano, 2022)
A simple, reliable, and self-switchable spin–orbit torque (SOT)-induced magnetization switching in a ferromagnetic single layer is needed for the development of next generation fully electrical controllable spintronic devices. In this work, field-free SOT-induced magnetization switching in a CoPt single layer is realized by broken multiple inversion symmetry through simultaneously introducing both oblique sputtering and a vertical composition gradient. A quantitative analysis indicates that multiple inversion asymmetries can produce dynamical bias fields along both z- and x-axes, leading to the observed field-free deterministic magnetization switching. Our study provides a method to accomplish fully electrical manipulation of magnetization in a ferromagnetic single layer without the external magnetic field and auxiliary heavy metal layer, enabling flexible design for future spin–orbit torque-based memory and logic devices.